Evaluation of severity of foliar diseases of mulberry under organic versus conventional farming systems (The Journal of Plant Protection Sciences, 2023)
Mulberry (Morus sp.), the sole food plant of  silkworm (Bombyx mori) is prone to several  foliar diseases caused by fungi, bacteria, virus  and mycoplasma. Among them, powdery mil dew (Phyllactinia corylea), leaf rust  (Peridiopsora mori), Pseudocercospora leaf  spot (Pseudocercospora mori), Myrothecium  leaf spot (Myrothecium roridum) and sooty  mold (Ascomycetes and Deutoromycetes  fungi) are major foliar diseases of mulberry in  the eastern and north eastern India (7,8).  About 10-15% leaf yield loss occurs due to powdery mildew, leaf rust and leaf spot dis eases (3,9). Besides, these diseases also re duce leaf quality drastically leading to poor  silkworm rearing. Qadri et al. (11, 12) re ported crop loss up to 54.56% and 55.59% at  maximum disease severity of leaf spot and  powdery mildew, respectively.
Keywords: evaluate foliar; diseases are generally